Analisis hubungan tingkat pengetahuan masyarakat terhadap perilaku swamedikasi nyeri rasional di Kecamatan Toribulu, Kabupaten Parigi Moutong - Afriani Kusumawati; Ririen Hardani; Fiska Devi; Indah Ismiranti (University Of Darussalam Gontor, 2025)
People often practice self-medication for common illnesses, using modern or traditional medicines without a doctor’s prescription. Pain, a sensation signaling tissue damage, is a common reason for self-medication. This study examines the relationship between knowledge levels and rational self-medication behavior for pain in Toribulu sub-district, Parigi Moutong Regency, Central Sulawesi. Using a descriptive approach, data were collected through purposive sampling. Questionnaires, tested for validity and reliability, were distributed to 391 respondents meeting inclusion criteria. Data analysis employed SPSS 23 with the Spearman correlation test. Results show 43.5% of respondents had high knowledge levels, 36.6% had sufficient levels, and 19.9% had poor levels. Regarding self-medication behavior, 60.1% displayed good behavior, 39.9% moderate behavior, and none poor behavior. The Spearman test revealed a significant but weak positive correlation (ρ-value = .000; correlation coefficient = .244) between knowledge levels and self-medication behavior. This indicates that while higher knowledge correlates with better behavior, its influence is minimal in improving self-medication practices within the community.